2008
DOI: 10.1016/j.psyneuen.2008.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Psychological stress impairs the local CD8+ T cell response to mucosal HSV-1 infection and allows for increased pathogenicity via a glucocorticoid receptor-mediated mechanism

Abstract: Summary Psychological stress and its associated increases in corticosterone are generally immunosuppressive and contribute to increased herpes simplex virus (HSV)-associated pathogenicity. However, the impact of stress on local control of the initial mucosal-based HSV infection has not been elucidated, nor have the ramifications of such failures of the immune response in terms of viral spread. To address these gaps in knowledge, the studies described herein sought to determine how psychological stress and asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 60 publications
1
27
0
3
Order By: Relevance
“…We have previously reported that our model of restraint stress increases serum corticosterone levels to approximately 300 ng/mL, whereas food-andwater-deprived control mice have serum corticosterone levels of less than 100 ng/mL (Ashcraft et al, 2008). Consistent with our hypothesis, mice that experienced restraint stress displayed more extensive vaginal pathology than did mice that were food-and-water deprived throughout infection (Figure 1).…”
Section: Glucocorticoids Increase the Severity Of Vaginal Infectionsupporting
confidence: 88%
See 3 more Smart Citations
“…We have previously reported that our model of restraint stress increases serum corticosterone levels to approximately 300 ng/mL, whereas food-andwater-deprived control mice have serum corticosterone levels of less than 100 ng/mL (Ashcraft et al, 2008). Consistent with our hypothesis, mice that experienced restraint stress displayed more extensive vaginal pathology than did mice that were food-and-water deprived throughout infection (Figure 1).…”
Section: Glucocorticoids Increase the Severity Of Vaginal Infectionsupporting
confidence: 88%
“…Such studies have indicated that psychological stress and associated neuroendocrine peptides and hormones are generally immunosuppressive. Despite the multitude of studies on restraint stress during primary HSV-1 infection (Anglen et al, 2003;Ashcraft et al, 2008;Bonneau et al, 1993b;Bonneau et al, 1991;Brenner and Moynihan, 1997;DeLano and Mallery, 1998;Nair et al, 2007;Ortiz et al, 2003), there have been no publications on the effect of stress on primary vaginal HSV-1 infection. Therefore, the studies presented here aimed to determine the impact of restraint stress during primary vaginal HSV-1 infection on the number and function of immune cells governing both the innate and adaptive immune response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychosocial stress has been correlated with oral herpes recurrences in humans (8). Psychological stress at the time of infection increases HSV-1 titers and pathology following intranasal or vaginal infection in mice (7,9). Epinephrine (EPI), a catecholaminergic hormone secreted by the adrenal medulla to induce the "short-term" fight-or-flight stress response, is regulated by the sympathetic nervous system.…”
mentioning
confidence: 99%